Revealing the News Frame of Democrat Party's Extraordinary Congress in Sibolangit: Power Intervention or Internal Conflict? - Nanang Krisdinanto; Theresia Intan Putri Hartiana (Jurnal Komunikasi Profesional, 2023)
This study aims to reveal the frame for reporting on the political events of the Sibolangit Party KLB that occurred in March 2021, starting with the assumption that news is not only an incident report but also a reality construction practice carried out by journalists with various contexts or interests that surround it. In the political context, the practice of mass media reporting in Indonesia is often connected with the struggle for political power. This issue is what we want to unravel from the news about the Democrat Party KLB published by the four online media with the highest traffic in Indonesia based on alexa.com, namely okezone.com, tribunnews.com, detik.com and kompas.com. This research wants to see what kind of news frame is developed by each media, and how it is connected with the political context that surrounds it. This study uses a qualitative-descriptive approach, and the method of framing analysis developed by Gamson & Modigliani. The results of the study indicate that there are differences in the frames that are packaged in each media. Detik.com and okezone.com seem to develop a frame that the political events of the Democratic Party KLB are the product of engineering and power intervention outside the party (Presidential Palace). On the other hand, kompas.com and tribunnews.com tend to develop a frame that the KLB of the Democratic Party is the product of an internal political struggle without government intervention.